A Nomogram for Predicting Intraoperative Hemodynamic Instability in Patients With Pheochromocytoma - Zhang, Zhiqiang; Ye, Yunlin; Yu, Jiajie; Liao, Shufen; Pan, Weibin; Guo, Yan; Jiang, Shuangjian; Luo, Cheng; Zheng, Fufu (Frontiers in Endocrinology, 2022)
Purpose: Surgical removal of pheochromocytoma (PCC) is the cornerstone of therapy, which is associated with high risk of intraoperative and postoperative life-threatening complications due to intraoperative hemodynamic instability (IHD). This study aims to develop and validate a nomogram based on clinical characteristics as well as computed tomography (CT) features for prediction of IHD in pheochromocytoma surgery. Methods: The data from 112 patients with pheochromocytoma were collected at a single center between January 1, 2010 and December 31, 2019. Clinical and radiological features were selected with the least absolute shrinkage and selection operator regression analysis to predict IHD then constituted a nomogram. The performance of the nomogram was assessed in terms of discrimination, calibration and clinical utility. Results: Age, levels of catecholamines and their metabolites, body mass index, laterality, Mayo Adhesive Probability score, and necrosis were identified as risk predictors of the presence of IHD. The nomogram was then developed using these six variables. The model showed good discrimination with C-index of 0.776 (95% CI, 0.683-0.868) and an area under the receiver operating characteristic curve (AUC) of 0.761 (95% CI, 0.665–0.856). The calibration plot suggested good agreement between predicted and actual probabilities. Besides calibration was tested with Hosmer–Lemeshow test (P = 0.903). Decision curve showed the clinical effectiveness of the nomogram. Conclusions: Our nomogram based on clinical and CT parameters could facilitate the treatment strategy according to assessing the risk of IHD in patients with pheochromocytoma.